2019
DOI: 10.1016/j.gloplacha.2019.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Fluvial terrace formation and its impacts on early human settlement in the Hanzhong basin, Qinling Mountains, central China

Abstract: The Qinling Mountains (QLM) form the climatic boundary between the temperate north and subtropical south of China. Many important Paleolithic archaeological sites located on fluvial terraces in this area have been reported in recent decades. Abundant artifacts have been excavated in silt layers overlying fluvial gravels and coarse sands. These silt layers have thus far been interpreted as aeolian deposits. However, in principle they could also represent (in part) fluvial (floodplain) deposits, especially near … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 68 publications
4
16
0
1
Order By: Relevance
“…Combined with the large width of the surfaces, this implies an important contribution to the transport of sediment by surface runoff. This interpretation is in agreement with Yang et al (2019) as their results also indicate episodic deposition of coarse sediment in aeolian deposits on terrace levels T2 (11 km to the east of the Baoshan section) and T4 (in the west of the Hanzhong Basin). They suggest that this component is deposited by temporary overland flowing water or, alternatively, that it reflects the presence of pedogenic nodules that were not dissolved during the pre-treatment process.…”
Section: Interpretation Of the End-member Mixing Modelsupporting
confidence: 91%
See 3 more Smart Citations
“…Combined with the large width of the surfaces, this implies an important contribution to the transport of sediment by surface runoff. This interpretation is in agreement with Yang et al (2019) as their results also indicate episodic deposition of coarse sediment in aeolian deposits on terrace levels T2 (11 km to the east of the Baoshan section) and T4 (in the west of the Hanzhong Basin). They suggest that this component is deposited by temporary overland flowing water or, alternatively, that it reflects the presence of pedogenic nodules that were not dissolved during the pre-treatment process.…”
Section: Interpretation Of the End-member Mixing Modelsupporting
confidence: 91%
“…Although the fluvial deposits at the base of the Baoshan section (profile D) show a similar shape-size trend; profile E is characterized by overall significantly lower aspect ratios. Similar findings are reported in Yang et al (2019), where it is shown that fluvial deposits have slightly lower aspect ratios with relatively large variations compared with the loess deposits.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…This region has been studied mainly for its aeolian loesspaleosol sequences interbedded with slack-water deposits covering river terraces. From bottom to top, the stratigraphic sequence is composed of fluvial gravel, alluvial sand interbeds, and ultimately loess and soils (Lu et al, 2011(Lu et al, , 2017Zhou et al, 2016;Sun et al, 2017;Yang et al, 2019). Yang et al (2019) have shown the gradual floodplain development of the second and fourth terraces as a result of channel incision during a climate transition from cold to warm.…”
Section: Geographical and Tectonic Settingmentioning
confidence: 99%